PENGARUH PENYULUHAN MENYIKAT GIGI DENGAN MEDIA TIKTOK TERHADAP NILAI PHP KELAS V SDN CIBURUY BANDUNG.docx - Damayanti, Rida; Supriyanto, Irwan; Widyastuti, Tri; Restuning, Sekar (Jurnal Terapi Gigi dan Mulut, 2024)
PHP (Patient Hygiene Performance) developed by Podsadley and Haley initially aimed to evaluate an individual's ability to clean dental debris after receiving brushing instructions. TikTok is used as an audio-visual counseling medium for dental health. This study aims to determine the influence of counseling on how to brush teeth with TikTok media on the PHP score of grade V students.Keywords: elementary school age children, tiktok media, PHP grades. The kind of study that is done is a pre-experimental design, involving one group that is given a pre-test and a post-test without a control group. Sampling was carried out using the total sampling technique. The variables in this study are counseling with TikTok media and PHP scores of grade V students. The counseling media has been tested and declared feasible by material experts and media experts. Hypothesis tests were carried out using the Wilcoxon test. The average PHP score before the intervention was 4.27 and increased to 8.49 after the intervention. The analysis of the Wilcoxon Sign Rank Test showed a p-value of 0.000 (<0.05), which indicates a significant influence of counseling using TikTok media on PHP valuesThe study's conclusions show that counseling on how to brush teeth with TikTok media has a significant influence on the PHP score of grade V students.